Besediloslovna primerjava pisne produkcije tujih in rojenih govorcev slovenščine - Petric Lasnik, Ivana (Jezik in slovstvo, 2004)
The article is an attempt to answer the question of how successful foreign speakers of Slovene are when having to produce a lengthy written text; the rate of success is mesasured against the texts produced by native speakers of Slovene. Both groups of texts are compared according to the chosen criteria, with the main focus placed on the criteria of cohesion and coherence as applied in text linguistics. The research was aimed at discovering what the purpose and reason for using a particular cohesive device were, what effect aparticular cohesive device achueves in the text, and how it could influence comprehension of the meaning of the text.
Keywords: Slovene; slovenščina; slvoenščina kot drugi ali tuji jezik; koherenca; kohezija; tekstna lingvistika